Synthesis, Anticonvulsant Evaluation and Molecular Docking Studies of Novel Benzo[1,3]dioxol-5-yloxy-N′-(4-substituted benzylidene)acetohydrazide Derivatives - Singh, Shailesh Kumar; Tripathi, Laxmi (Asian Journal of Chemistry, 2019)
Novel (benzo[1,3]dioxol-5-yloxy)-N′-(4-substituted benzylidene)acetohydrazide derivatives were synthesized and their anticonvulsant activity evaluated by MES and scMET seizure models. Compound 2-(benzo[d][1,3]dioxol-5-yloxy)-N′-benzylideneacetohydrazide (4a) was found to be most potent in MES seizure test and showed no neurotoxicity at the highest administered dose. All the compounds showed high docking score with γ-aminobutyric acid receptor, GABAAR-β3 homopentamer (PDB ID: 4COF). Thus, the probable mechanism of action of benzo[1,3]dioxol-5-yloxy-N′-(4-substituted benzylidene)acetohydrazide derivatives (4a-h) may be augmentation of GABAergic activity.